HUBUNGAN MOTIVASI BELAJAR DAN PERSEPSI SISWA TERHADAP PELAJARAN MATEMATIKA DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP N 1 JETIS - Nur Khasanah; Benedictus Kusmanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this research is to find out the correlation between motivation to learn and students perception on mathematics with the results ofÂ mathematics learning. This research method applied descriptive of correlation.The population in this research is grade VIII SMP N 1 Jetis totaling 180 students, with a sample of 120 students taken by cluster random sampling. Analytical techniques multiple regression analysis with requirment of normality and linierity. Based on the results of the research, R = 0,460, meaning that there was a positive correlation between motivation to learn and students perception on mathematics with the results of mathematics learning. Rx1.y â€“ x2 = 0,204, meaning that therewas a positive correlation between motivation to learn with the results of mathematics learning. Rx2.y â€“ x1 = 0,314, meaning that there was a positive correlation between students perception on mathematics with the results of mathematics learning.